PENGARUH SUPLEMENTASI MINYAK SAWIT MERAH TERHADAP KADAR HS-CRP TIKUS MALNUTRISI - Astani, Ameliora; Milasari, Novi; Rosalina, Rosalina; Supriono, Supriono (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Red palm oil (RPO) is a processed product derived from oil palm that is rich in β-carotene, a precursor of vitamin A. Vitamin A is known to play a beneficial role in reducing inflammatory responses, which are among the risk factors that exacerbate stunting. This study aimed to evaluate the effectiveness of RPO in reducing levels of the inflammatory marker high-sensitivity C-reactive protein (Hs-CRP). It is expected that RPO supplementation may help suppress inflammation, thereby contributing to the improvement of nutritional status. An in vivo experimental design was employed using male Sprague Dawley rats, which were divided into five groups: a healthy control group (K+), a malnourished group (K−), and three treatment groups receiving RPO at different dosages (P1: 0.16 ml/200 g BW/day; P2: 0.26 ml/200 g BW/day; and P3: 0.56 ml/200 g BW/day). The intervention lasted for eight weeks, consisting of a four-week malnutrition induction phase followed by a four-week RPO supplementation phase. RPO administration resulted in a significant increase in body weight among the malnourished rats in all treatment groups (P1, P2, and P3) (p < 0.05). However, Hs-CRP levels did not show statistically significant changes following RPO supplementation in malnourished rats. The potential of red palm oil in mitigating malnutrition warrants further investigation by considering inflammatory markers and conducting a comprehensive analysis of vitamin A status.